Delineating the pattern of treatment for elderly locally advanced NSCLC and predicting outcomes by a validated model: A SEER based analysis. (3rd April 2019) - Guo, Meiying; Li, Butuo; Yu, Yishan; Wang, Shijiang; Xu, Yiyue; Sun, Xindong; Wang, Linlin; Yu, Jinming
Abstract: Introduction: Locally advanced nonsmall‐cell lung cancer (LA‐NSCLC) represented a highly heterogeneous group, with more than half of the patients aged ≥65 years at the time of diagnosis. However, the optimal treatment for elderly LA‐NSCLC patients was still not defined. Methods: A total of 33530 elderly patients (≥65 years) diagnosed with LA‐NSCLC from 2004 to 2014 were identified from Surveillance, Epidemiology, and End Results (SEER) database. Results: Locally advanced nonsmall‐cell lung cancer patients aged 65‐74 years were more frequently treated with chemoradiotherapy (CRT) (40%), while patients aged ≥75 years received more best supportive care (BSC) (36%). For age group of 65‐74 years, patients who had surgery with or without (neo)adjuvant therapy had a median survival of 28 months, CRT 15 months, radiotherapy (RT) alone 6 months, chemotherapy alone 11 months, and BSC 3 months; while for patients aged ≥ 75 years, the median OS was 20, 13, 7, 9, and 2, respectively. Besides, independent clinicopathological factors were integrated into nomograms for OS and CSS prediction, C‐indexes achieved 0.692 and 0.698, respectively. Importantly, the discrimination of nomogram was superior to that of the American Joint Committee on Cancer TNM classification (0.742 vs 0.572 for training set and 0.731 vs 0.565 for validation set). Conclusion: For elderly patients with LA‐NSCLC, the curative‐intent treatment (surgery or CRT) conferred better survival compared to chemotherapy alone, RT alone and BSC. The proposed nomograms based on independent clinicopathological variables may be practical and helpful for precise evaluation of patient prognosis, and guiding the individualized treatment for elderly LA‐NSCLC. Abstract : We aimed to delineate the treatment pattern in elderly patients with LA‐NSCLC and determine its prognostic role in patient outcomes based on Surveillance, Epidemiology, and End Results (SEER) database.